Bibliometric Analysis of Islamic Education Management Research Trends in Indonesia (2015-2025): Identifying Gaps and Strategies for Development - Aminudin, Aminudin; Cahyani, Dewi; Munawaroh, Mumun; Arifudin, Iis (JURNAL AL-TANZIM, 2025)
This study aims to analyze trends and developments in Islamic education management research in Indonesia from 2015 to 2025. The method employed is bibliometric analysis, utilizing a quantitative approach. This study includes 107 documents published by 371 authors, with an average document age of 3.02 years. This bibliometric analysis uses VOSviewer and Biblioshiny software. This study found a significant surge in Islamic Education Management publications in Indonesia, with an annual growth rate of 21.48%, particularly in 2022 and 2023, and a notable contribution from religious universities, such as UIN Sunan Kalijaga. The change in topics indicates a shift from a normative approach towards digitalization, interdisciplinarity, and technology-based institutional strategies, including responses to crises such as the pandemic. However, a significant gap remains in integrative studies that combine applied science with cutting-edge research technology, presenting strategic opportunities for the future development of Islamic Education Management research. This research provides a data-driven reference for developing a national research strategy in Islamic Education Management and a roadmap for scientific collaboration. Further research can focus on strengthening interdisciplinary research, integrating digital technologies, and collaborative networks across countries and institutions.